Q: What is -4 equals 9x plus 23?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

9x + 4 = 6 9x = 6 -4 9x = 2 x = 2/9

44 = 9x +8 36=9x 4=x

9x + 2 = 12x + 14 -3x = 12 x = -4

9x-11 = 6x+1 9x-6x = 1+11 3x = 12 x = 4

4x+3=9x-4+4 +44x+7=9x-4x -4x7=5x-------57/5=1.41.4=x

Related questions

9x + 4 = 6 9x = 6 -4 9x = 2 x = 2/9

44 = 9x +8 36=9x 4=x

-9x + 4 = -50 -9x = -50 - 4 -9x = -54 -x = -6 x = 6.

7x-4=9x+10-14=2xx=-7

9x + 2 = 12x + 14 -3x = 12 x = -4

9x-4 = 7x+8 9x-7x = 8+4 2x = 12 x = 6

9x+4 =x-7 8x=-3 x=-3/8

x=2/3

9x-11 = 6x+1 9x-6x = 1+11 3x = 12 x = 4

4x+3=9x-4+4 +44x+7=9x-4x -4x7=5x-------57/5=1.41.4=x

minus 4 plus 9 = 5, so 5x

5.4 = (9x+4)/5 - 813.4 = (9x+4)/567 = 9x+463 = 9x7 = xYour answer is 7.